Linkages and Efficiency Between iTraxx Europe and Financial Market Dynamics in South-East Europe Capital Markets in Post-crisis Period - Mariya Georgieva Paskaleva; Ani Stoitsova-Stoykova (International Journal of Economics and Financial Issues, 2017)
We examine the market efficiency and the linkages between financial market dynamics and iTraxx Europe of the equity markets of South East Europe (SEE). Therefore, this study aims to answer whether there exists a difference between the stock market performance of the developed and emerging SEE capital markets. This paper employs GARCH model and Granger causality test. We use the returns of iTraxx Europe and the daily returns of five SEE stock market indices - Bulgaria, Croatia, Slovenia, Turkey and Romania over the period after the financial crisis of 2008. The results reveal that SEE capital markets except Bulgaria and Slovenia aren't efficient in the context of the efficient market hypothesis (EMH). Moreover, the iTraxx Europe affects the financial market dynamics of SEE stock indices. The analysis shows that the Itraxx Europe Granger-cause stock market returns with less significant causal relations from stock market returns to iTraxx Europe.